Innovative Experiences In Access To Finance : Market Friendly Roles For The Visible Hand ? - Torre, Augusto de la 1997- (The World Bank, 2007)
Interest in access to finance has increased significantly in recent years, as growing evidence suggests that lack of access to credit prevents lower-income households and small firms from financing high return investment projects, having an adverse effect on growth and poverty alleviation. This study describes some recent innovative experiences to broaden access to credit. These experiences are consistent with an emerging new view that recognizes a limited role for the public sector in financial markets, but contends that there might be room for well-designed, restricted interventions in collaboration with the private sector to foster financial development and broaden access. The authors illustrate this view with several recent experiences in Latin America and then discuss some open policy questions about the role of the public and private sectors in driving these financial innovations